Long-term outcome and quality of life in patients with iliac vein compression syndrome after endovascular treatment. (September 2019) - Bi, Yonghua; Yu, Zepeng; Chen, Hongmei; Ren, Jianzhuang; Han, Xinwei
Purpose: Deep venous thrombosis induced by iliac vein compression syndrome often interferes with patients' work or daily living. This study aims to investigate the long-term outcome and quality of life in patients with iliac vein compression syndrome after endovascular treatment. Methods: From October 2011 until June 2016, 28 patients with acute deep venous thrombosis diagnosed as iliac vein compression syndrome by ultrasonography were enrolled in this perspective study. Fifteen patients underwent balloon dilation and stent insertion (group A); 13 patients received anticoagulation treatment, thrombolysis, or balloon dilation without stenting (group B). The Medical Outcomes Study-Short Form-36 was used to assess the quality of life preoperatively and after endovascular treatment. The follow-up of Short Form-36 questionnaire was obtained within 12.13 ± 12.04 months after repair. Results: There was no operative mortality in two groups, and technical success was achieved in 14 (93.3%) patients in group A. Thirteen (86.7%) patients were cured in group A, which was significantly higher than that of group B (46.2%, p  = 0.042). Only one patient showed occlusion of stent in group A, with a secondary patency rate of 93.3%. Except for 'Role emotion', all remaining domains were significantly improved in group A when compared with preoperative score ( p  < 0.01). The scores of 'Physical functioning', 'Role physical', and 'General health' in group A were significantly higher than those of group B ( p  < 0.05). Conclusions: Endovascular stenting to treat iliac vein compression syndrome shows beneficial clinical outcome, cumulative patency rate, and quality of life, with high technical success and low complications.